2022
DOI: 10.1371/journal.pone.0270588
|View full text |Cite
|
Sign up to set email alerts
|

Research on capital allocation efficiencies with four-dimensional factor capitals from China’s intelligent manufacturing enterprises

Abstract: Compared with traditional manufacturing enterprises, intelligent manufacturing enterprises pay more attention to the investment of knowledge capital and technological capital. Taking 258 intelligent manufacturing listed companies in China from 2015 to 2020 as research samples, the paper selects the material capital, human capital, knowledge capital and technological capital of enterprises as the input variables of Cobb-Douglas production function. Considering that enterprises are often affected by spatial corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Tey are both inputs made by enterprises in R&D activities and represent their ability to achieve breakthrough innovation. Tis is supported by the study of Wang et al [14], which found that both human capital and knowledge capital of the frms contribute to intelligent performance. Terefore, when considering the R&D investment of a company, the two must be included together, so as to objectively refect the actual degree of R&D investment of the company.…”
Section: Infuencing Factors Of Intelligent Manufacturingmentioning
confidence: 79%
“…Tey are both inputs made by enterprises in R&D activities and represent their ability to achieve breakthrough innovation. Tis is supported by the study of Wang et al [14], which found that both human capital and knowledge capital of the frms contribute to intelligent performance. Terefore, when considering the R&D investment of a company, the two must be included together, so as to objectively refect the actual degree of R&D investment of the company.…”
Section: Infuencing Factors Of Intelligent Manufacturingmentioning
confidence: 79%
“…By integrating and reconstructing knowledge and technology, technological talents transfer their professional and R&D knowledge to grassroots employees, thus improving overall workforce quality. In addition, their strong desire for knowledge and keen observation of technological talents enables them to quickly absorb advanced knowledge and technology and apply them to production operations [ 59 ], improve the technological innovation ability of enterprises, and then promote high-quality development of the manufacturing industry by enhancing production capacity [ 60 ], improving production processes, promoting product upgrading, and optimizing management modes.…”
Section: Analysis Of the Empirical Resultsmentioning
confidence: 99%
“…The quantitative research on regional IM is few, and the index system of IM is lacking. Compared with the analysis of the connotation of IM [10,29,59,60] and the theoretical model of a coupled coordination system between DE and IM constructed in this paper, the development level of IM in each provincial administrative region is comprehensively calculated from four dimensions of intelligent R&D investment, intelligent technology, intelligent products and intelligent application, considering the availability and quality of data. Finally, the index system of the DE and IM coupling systems with 8 factor layers and 24 index layers is selected.…”
Section: Index Compositionmentioning
confidence: 99%